Experience of mass casualty management - the Rana Plaza tragedy: An anesthesiologist’s perspectives at a peripheral military hospital in Bangladesh - Murshed, Hasan; Sultana, Rokshana (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: The worst factory disaster in the history of Bangladesh occurred when a nine-storied commercial building “Rana Plaza” collapsed outskirts of the capital city. In our hospital there were no documented guidelines for dealing with mass casualty incident. Our aim was to share the experience of managing mass casualty. Methods: Outcome of working experience based on four principles issues (assessment of available resources, ensuring critical but limited care, stocking up medicine and equipment for patient surge, tough rationing of decision) was assessed retrospectively. Clinical records of 155 patients were investigated. The discharge diagnosis, x-ray or computerized tomography was used for verification of injuries. Results: Among 431 patients reported to emergency and casualty department, 407 (94.431%) were admitted to hospital. Among them, 155 (35.9%) required anesthesia and/or intensive care. Most of the injuries were blunt trauma and soft tissue trauma. Other injuries included fractures, head and crush injuries. Majority of surgical procedure were wound debridment, fascitomy, amputation and external fixation. Most of the surgical procedures (85%) were performed under ketamine, 22 (15%) patients received different regional techniques and only one patient received general anesthesia. Injuries requiring definitive surgery were referred to different tertiary level hospital. One patient died of lethal injuries and all the others survived. Fifty one patients survived with disability. Conclusions: Anesthesiologists can improve patient care and hospital efficiency by optimizing facility utilization, surgical/anesthesia logistics, man power management, institutional communication, and leadership. Considering setup with limited workforce and equipment, management of mass casualty based on four simple principal issues might help others in managing such events. Journal of Society of Anesthesiologists of Nepal 2015; 2(1): 8-12